Methoxychalcones: Effect of methoxyl group on the antifungal, antibac-terial and antiproliferative activities - Marques, Beatriz C. [UNESP]; Santos, Mariana B. [UNESP]; Anselmo, Daiane B. [UNESP]; Monteiro, Diego A. [UNESP]; Gomes, Eleni [UNESP]; Saiki, Marilia F. C. [UNESP]; Rahal, Paula [UNESP]; Rosalen, Pedro L.; Sardi, Janaina C. O.; Regasini, Luis O. [UNESP] (Bentham Science Publishers, 2020)
Background: Chalcones substituted by methoxyl groups have presented a broad spec-trum of bioactivities, including antifungal, antibacterial and antiproliferative effects. However, a clear and unambiguous investigation about the relevance of this substituent on the chalcone framework has not been described. Objective: The purpose of this work is to assess the antibacterial, antifungal and antiproliferative activities of the two series of seventeen synthesized regioisomeric methoxychalcones. Series I and II were constituted by chalcones substituted by methoxyl groups on rings A (5–12) and B (13–21), respectively. In addition, the library of methoxychalcones was submitted to in silico drug-likeness and pharmacokinetics properties predictions. Methods: Methoxychalcones were synthesized and their structures were confirmed by NMR spectral data analyses. Evaluations of antimicrobial activity were performed against five species of Candida, two Gram-negative and five Gram-positive species. For antiproliferative activity, methoxychalcones were evaluated against four human tumorigenic cell lines, as well as human non-tumorigenic keratinocytes. Drug-likeness and pharmacokinetics properties were predicted using Molinspiration and PreADMET toolkits. Results: In general, chalcones of series I are the most potent antifungal, antibacterial and antipro-liferative agents. 3’, 4’, 5’-Trimethoxychalcone (12) demonstrated potent antifungal activity against Candida krusei (MIC = 3.9 µg/mL), eight times more potent than fluconazole (reference antifungal drug). 3’-Methoxychalcone (6) displayed anti-Pseudomonas activity (MIC = 7.8 µg/mL). 2’,5’-Dimethoxychalcone (9) displayed potent antiproliferative effect against C-33A (cervix), A-431 (skin) and MCF-7 (breast), with IC50 values ranging from 7.7 to 9.2 µM. Its potency was superior to curcumin (reference antiproliferative compound), which exhibited IC50 values ranging from 10.4 to 19.0 µM. Conclusion: Our studies corroborated the relevance of methoxychalcones as antifungal, antibacte-rial and antiproliferative agents. In addition, we elucidated influence of the position and number of methoxyl groups toward bioactivity. In silico predictions indicated good drug-likeness and phar-macokinetics properties to the library of methoxychalcones.
Keywords: Antibacterial; Antifungal; Antiproliferative; Chalcone; Drug-likeness; Methoxyl